The Effectiveness of Life Skills Technical Career Information Services to Improve Career Understanding Viewed from Career Planning Aspects - Hijrah Eko Putro; Indiati Indiati (STKIP Singkawang, 2023)
This research was conducted to know the effectiveness of career information services using Life Skills techniques for the career advancement of Al-Iman High School students in Magelang City in terms of career planning aspects. The research method is experimental research. The research design used a pre-experimental of one group pretest-posttest design. The population in this study were XII students, totalling 26 students. The sample was 8 students using non-random sampling with quota sampling technique. The data collection instrument in this study used a career planning questionnaire. The data analysis technique used the Paired sample t-test with the consideration that this study used one independent variable. The results of the effectiveness test of this study were that this career service was effective in improving student careers in terms of career planning aspects. The level of student career advancement increased after following career information with life skills techniques. This could be seen from the understanding of students' careers before and after being given career information with life skills techniques by 23% with details: self-understanding indicators 10%, communicate and cooperate indicators 28%, improve self-performance 24%, get to know the world of social work21% and strengthened through an effectiveness test using a t-test which showed -t count (-4.894) < -t table (-2.365).